The Effectiveness of Grant Support for Doctoral Students in Russia: A Quasi-Experimental Analysis of the RFBR Programme - N. M. Smirnov (Высшее образование в России, 2025)
The study examines the effects of the Russian Foundation for Basic Research grant programme for doctoral students. It analyses the impact of the programme, implemented in 2019–2020, designed to support dissertation research among doctoral candidates. The study investigates the effects of receiving a grant on doctoral students’ outcomes and scientific productivity, specifically their successful thesis defense and publication activity. A quasi-experimental design is employed, utilizing Propensity Score Matching (number of students in the experimental group N = 1 073). The results demonstrate that receiving a grant significantly increases the likelihood of successful thesis defense – grant recipients are 70% more likely to defend successfully compared to non-recipients, all other things being equal. Grant recipients are also more likely to complete their dissertations within the standard timeframe. Furthermore, receiving a grant positively influences doctoral students’ publication activity. The effect of the grant does not differ based on the gender or the type of institution. These findings underscore the importance of financial support for successful dissertation completion and encourage further research into the mechanisms by which various forms of financial support influence doctoral students’ outcomes, as well as comparative studies on the effectiveness of grants versus other forms of support.